BARIUM STANNATE-CONTAINING Ni PASTE, MULTILAYER CERAMIC CAPACITOR, AND MANUFACTURING METHOD THEREOF

JP2025028707APending Publication Date: 2025-03-03DAIKEN CHEM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2023133683
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-03-03

AI Technical Summary

Benefits of technology

【0018】 本発明の一形態によれば、電圧印加時における信頼性が高く、高温負荷寿命の長いMLCCの、内部電極を形成することのできるNiペーストを提供することができる。本発明の一形態によれば、焼成時に内部電極の途切れとそれに伴う容量低下を招くおそれの少ないMLCCの内部電極形成用Niペーストを提供することができる。本発明の一形態によれば、焼成に伴って内部電極層から誘電体層へと拡散し、誘電率や、誘電損失、MLCCの温度特性等に悪影響を与えるおそれのある元素をなるべく含有していない、MLCCの内部電極形成用Niペーストを提供することができる。本発明の一形態によれば、上記のような内部電極形成用Niペーストの製造方法を提供することができる。本発明の一形態によれば、上記のような内部電極形成用Niペーストを用いたMLCCの製造方法を提供することができる。本発明の一形態によれば、上記のような内部電極形成用Niペーストを用いて製造することのできるMLCCを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028707000001_ABST
    Figure 2025028707000001_ABST
Patent Text Reader

Abstract

To provide: a Ni paste that can suppress the occurrence of breaks in an internal electrode during firing in the manufacture of a multilayer ceramic capacitor (MLCC), improve the manufacturing yield, and improve the high-temperature load life; an MLCC that exhibits excellent reliability even when the dielectric layer is further thinned and a voltage of high electric field strength is applied; and a method for manufacturing the same.SOLUTION: In a Ni paste used for forming an internal electrode of an MLCC, barium stannate powder is added as a co-material in addition to nickel powder, a binder, and a solvent. The Ni paste preferably further contains barium titanate powder, and more preferably contains barium titanate powder containing sulfur.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Ni paste used for forming internal electrodes of a multilayer ceramic capacitor and a method for producing the same, as well as a multilayer ceramic capacitor and a method for producing the same. [Background technology]

[0002] With the recent progress in information and communication technology, multilayer ceramic capacitors (hereinafter also referred to as MLCCs) are required to be smaller and have larger capacitance. To meet this demand, the dielectric layers and internal electrode layers that constitute multilayer ceramic capacitors are being made more multilayered and thinner. However, when the internal electrode layers are made thinner, there is a problem that the electrodes are more likely to be disconnected during firing, which reduces the manufacturing yield. In addition, when the dielectric layers are made thinner, the electric field strength in the laminate formed by alternately stacking the dielectric layers and the internal electrode layers increases, and the internal electrode layers are subjected to a large electrostatic attraction force. Therefore, there is a demand for improved reliability when voltage is applied.

[0003] In general, a multilayer ceramic capacitor is manufactured as follows. Metal powder such as Ni powder and dielectric ceramic powder are dispersed in a vehicle made of a binder and a solvent to form a metal paste, which is used as an internal electrode material, and is applied to ceramic green sheets, which are dielectric ceramic substrates, by screen printing or the like. Next, a multi-layered laminate of the ceramic green sheets is laminated in a lamination and compression process, and integrated by heat and pressure. Furthermore, the binder is removed at 500°C or less in an oxidizing or inert atmosphere, cut to a predetermined size, and then fired in a reducing atmosphere to produce an MLCC.

[0004] Traditionally, precious metals such as Pd have been used for the internal electrodes of MLCCs. In recent years, due to cost considerations, internal electrodes mainly made of Ni have been used. When manufacturing MLCCs whose internal electrodes mainly consist of Ni by firing, the firing must be carried out in a reducing atmosphere to prevent oxidation of the Ni. During this process, oxygen defects are introduced into the dielectric layer, which causes a problem of reduced high-temperature load life.

[0005] Patent Document 1 discloses that adding Sn to an internal electrode mainly composed of Ni changes the height of the electrical barrier at the interface between the dielectric layer and the electrode layer, thereby extending the high-temperature load life of the MLCC. As a mode of the internal electrode, an internal electrode in which Sn is dissolved in Ni is described. As a mode of adding Sn, it is described that the internal electrode is formed using a Ni paste containing Ni-Sn alloy powder or a Ni paste containing tin oxide powder represented by SnO or SnO2.

[0006] Patent Document 2 discloses that the high temperature load life of an MLCC can be extended by configuring the internal electrodes in such a manner that at least one metal selected from the group consisting of In, Ga, Zn, Bi, and Pb is dissolved in Ni.

[0007] Patent Document 3 discloses that the high temperature load life of an MLCC can be improved by forming an internal electrode from a Ni paste for internal electrodes that contains a pyrochlore-type oxide that includes Sn and either or both of Ta and Nb. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Restated WО2015-016309 publication [Patent Document 2] Restated WО2015-087688 publication [Patent Document 3] Restatement WО2020-090415 publication Summary of the Invention [Problem to be solved by the invention]

[0009] According to the techniques described in Patent Documents 1 to 3, the high temperature load life of an MLCC can be extended to some extent, but the following problems still remain. In the technology described in Patent Document 1, Sn dissolves in Ni, lowering the melting point of Ni, and the dispersibility of the tin oxide powder is very important, and if the tin oxide powder is not uniformly dispersed, the tin oxide powder and Ni will be present locally, which will promote the sintering of the internal electrode layer during firing, causing ball-up in various places, which is likely to lead to breakage of the internal electrodes and the associated decrease in capacity. In addition, it is necessary to change the composition of the dielectric material according to the sintering temperature of the electrodes, which makes it less versatile and limits its uses. In the technology described in Patent Document 2, In, Ga, Zn, Bi and / or Pb added to the internal electrodes diffuses into the dielectric layer during firing, which may change the firing temperature of the MLCC and adversely affect the dielectric constant, dielectric loss, temperature characteristics of the MLCC, etc. Furthermore, not only are Pb and Bi only used in MLCCs with specific characteristics, and their use is limited, but it is also expected that regulations on the use of Pb will become stricter in the future due to environmental damage. In the technology described in Patent Document 3, the Ta-based or Nb-based Sn oxide contained in the internal electrode layer is an oxide with a pyrochlore structure, while the BaTiO3 constituting the dielectric layer is an oxide with a perovskite structure, and the structures do not match and have poor affinity. Therefore, during firing, localized sintering unevenness occurs at the interface between the internal electrode layer and the dielectric layer, causing abnormal grain growth, which is likely to lead to discontinuity of the internal electrode and the associated decrease in capacity. In addition, Ta or Nb may diffuse from the internal electrode layer to the dielectric layer during firing, changing the firing temperature of the MLCC and adversely affecting the dielectric constant, dielectric loss, temperature characteristics of the MLCC, etc. Furthermore, Ta or Nb is a rare earth whose ore deposits and production are almost all dependent on Brazil, and there are also uncertainties in terms of supply and price.

[0010] Therefore, the object of the present invention is, first, to provide a Ni paste capable of forming an internal electrode of an MLCC having high reliability when a voltage is applied and a long high-temperature load life, or, second, to provide a Ni paste for forming an internal electrode of an MLCC that is unlikely to cause the internal electrode to be broken during firing and the associated capacity reduction, or, third, to provide a Ni paste for forming an internal electrode of an MLCC that contains as little elements as possible that may diffuse from the internal electrode layer to the dielectric layer during firing and adversely affect the dielectric constant, dielectric loss, temperature characteristics of the MLCC, etc. Alternatively, the object of the present invention is to provide a method for manufacturing the Ni paste for forming an internal electrode as described above. Alternatively, the object of the present invention is to provide a method for manufacturing an MLCC using the Ni paste for forming an internal electrode as described above. Alternatively, the object of the present invention is to provide an MLCC that can be manufactured using the Ni paste for forming an internal electrode as described above. The present invention has been made to solve at least one of the above problems. [Means for solving the problem]

[0011] A first aspect of the present invention is a Ni paste for forming an internal electrode of a multilayer ceramic capacitor, the Ni paste containing nickel powder and ceramic powder, the ceramic powder containing barium stannate.

[0012] A second aspect of the present invention is the Ni paste of the first aspect, wherein the ceramic powder further contains barium titanate powder.

[0013] A third aspect of the present invention is the Ni paste according to the first or second aspect, wherein the ceramic powder further contains sulfur-containing barium titanate powder.

[0014] The fourth aspect of the present invention is the third aspect, wherein the barium stannate is mixed with the nickel powder. The barium titanate powder or the sulfur-containing barium titanate powder is contained in a ratio of 1 to 5 mass % relative to the nickel powder, and the barium titanate powder or the sulfur-containing barium titanate powder is contained in a ratio of 5 to 25 mass % relative to the nickel powder.

[0015] A fifth form of the present invention is a method for producing a Ni paste for forming an internal electrode of a multilayer ceramic capacitor, in which nickel powder, barium titanate powder or barium titanate powder containing sulfur, and barium stannate powder are mixed into a vehicle in which a binder and a solvent are dissolved to produce a Ni paste.

[0016] A sixth aspect of the present invention is a method for producing a multilayer ceramic capacitor, comprising coating the Ni paste according to the first, second or fourth aspect on a ceramic substrate and firing the coated substrate to form an internal electrode containing Ni.

[0017] A seventh form of the present invention is a multilayer ceramic capacitor comprising: a ceramic laminate formed by alternately laminating a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni; and an external electrode formed on an outer surface of the ceramic laminate, wherein the internal electrode layers contain elements Ba, Ti, O, Sn, and S. Effect of the Invention

[0018] According to one embodiment of the present invention, it is possible to provide a Ni paste capable of forming an internal electrode of an MLCC having high reliability during voltage application and long high-temperature load life. According to one embodiment of the present invention, it is possible to provide a Ni paste for forming an internal electrode of an MLCC that is unlikely to cause the internal electrode to be broken during firing and the associated capacity reduction. According to one embodiment of the present invention, it is possible to provide a Ni paste for forming an internal electrode of an MLCC that contains as little elements as possible that may diffuse from the internal electrode layer to the dielectric layer during firing and adversely affect the dielectric constant, dielectric loss, temperature characteristics of the MLCC, and the like. According to one embodiment of the present invention, it is possible to provide a method for manufacturing the Ni paste for forming an internal electrode as described above. According to one embodiment of the present invention, it is possible to provide a method for manufacturing an MLCC using the Ni paste for forming an internal electrode as described above. According to one embodiment of the present invention, it is possible to provide an MLCC that can be manufactured using the Ni paste for forming an internal electrode as described above. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic cross-sectional view of a multilayer ceramic capacitor (MLCC). [Diagram 2] FIG. 2 is a cross-sectional photograph of the MLCC laminate according to the present invention after firing. [Figure 3A] FIG. 3A is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the measured capacitance value of an MLCC produced using the Ni paste. [Figure 3B] FIG. 3B is a continuation of FIG. 3A. [Figure 4] FIG. 4 is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the measured value of the DF (dielectric tangent) of the MLCC produced using the Ni paste. [Figure 5A] FIG. 5A is a graph (Weibull plot) showing the relationship between time t and failure rate F in a high-temperature load test of the MLCC according to the present invention. [Figure 5B] FIG. 5B is a continuation of FIG. 5A. [Figure 6]FIG. 6 is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the MTTF (mean time to failure) in a high-temperature load test of an MLCC produced using the Ni paste. [Figure 7] FIG. 7 is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the measured value of IR (insulation resistance) of an MLCC produced using the Ni paste. [Figure 8] FIG. 8 is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the measured value of TCC (temperature change of capacitance) of an MLCC produced using the Ni paste. [Figure 9] FIG. 9 is a graph showing the relationship between the amount of barium stannate added to the Ni paste according to the present invention and the measured values ​​of the capacitance and DF (dielectric tangent) of the MLCC produced using the Ni paste. [Figure 10A] FIG. 10A is a graph showing the relationship between the amount of co-material (barium titanate) added to the Ni paste of the present invention and various characteristics such as capacitance and MTTF (mean time to failure) of an MLCC produced using the Ni paste. [Figure 10B] FIG. 10B is a continuation of FIG. 10A. [Figure 11A] FIG. 11A is a graph showing how the characteristics of an MLCC produced using a Ni paste according to the present invention change depending on whether the barium titanate powder contains sulfur when the Ni paste contains barium titanate powder. [Figure 11B] FIG. 11B is a continuation of FIG. 11A. [Figure 12A] FIG. 12A is a graph showing the results of TMA (thermomechanical analysis) measurements on the Ni paste according to the present invention. [Figure 12B] FIG. 12B is a continuation of FIG. 12A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Next, the mode for carrying out the present invention will be described in detail. Note that the present invention is not limited to the embodiment and examples described below, and should be understood to include various modified forms and variations carried out within the scope of the technical idea of ​​the present invention.

[0021] In consideration of the fact that various problems occur when preparing Ni paste for forming internal electrodes of MLCCs using a method of dissolving Sn in nickel powder as in Patent Document 1 or a method of adding Sn containing other elements as in Patent Document 3, the present inventors have noticed that barium titanate, which is often used as a co-material for dielectric layers and Ni pastes, contains Ba, which has a sintering suppression effect, and have found that by mixing powder of barium stannate (BaSnO3), which has the same perovskite crystal structure as barium titanate, into a vehicle, it is possible to prepare Ni paste for forming internal electrodes of MLCCs with less breaks in the internal electrodes and a long high-temperature load life. The present invention was made based on this finding.

[0022] According to a first aspect of the present invention, there is provided a Ni paste for forming an internal electrode of a multilayer ceramic capacitor, the Ni paste containing nickel powder and ceramic powder, the ceramic powder containing barium stannate. According to this embodiment, the Ni paste contains tin, which has the effect of extending the high-temperature load life of MLCCs, in the form of a crystalline oxide called barium stannate, so it is possible to provide a Ni paste for forming internal electrodes which has less discontinuity in the internal electrodes and which has a longer high-temperature load life of MLCCs than when using nickel powder in which tin is dissolved in nickel. In addition, barium stannate (BaSnO3) contains Ba, which has a sintering inhibitory effect, and the crystal structure of barium stannate is the same perovskite structure as the crystal structure of barium titanate (BaTiO3), which is often used as a co-material for dielectric layers and Ni paste. Therefore, when the Ni paste of this embodiment is used to form internal electrodes of MLCCs whose dielectric layers are mainly composed of barium titanate, there is little risk of localized sintering unevenness occurring at the interface between the internal electrode layer and the dielectric layer during firing, and there is also little risk of the internal electrodes being broken and the resulting decrease in capacity. Furthermore, the Ni paste of this embodiment does not contain other elements such as In, Ga, Zn, Bi, Pb, Ta, and Nb that may diffuse from the internal electrode layer to the dielectric layer during firing and adversely affect the dielectric constant, dielectric loss, and temperature characteristics of the MLCC. Therefore, it can be used to form internal electrode layers of MLCCs with long high-temperature load life without sacrificing desired MLCC characteristics such as temperature characteristics. It can be used. The form in which barium stannate is contained in the Ni paste is not particularly limited. For example, barium stannate powder may be used as all or part of the ceramic powder, or the powder may be mixed.

[0023] The sintering suppression effect of Ba contained in barium stannate (BaSnO3) will be explained in more detail. It is known that in a sintered body of barium titanate (BaTiO3) with a perovskite structure, when the ratio of A site (Ba) to B site (Ti) is made A site (Ba) rich (i.e., the Ba / Ti ratio is made larger than 1), the sinterability is suppressed ("Microstructure Control and Grain Boundary Structure of BaTiO3 Sintered Body", Yamamoto Takehisa et al., Materia Japan, Vol. 38, No. 2 (1999)). In this embodiment, BaSnO3, which is a sintering suppressant added to the Ni paste, diffuses into the dielectric layer, which is mainly composed of BaTiO3, as the sintering of the internal electrodes progresses during firing. At this time, the A site (Ba) rich BaTiO3 near the interface between the internal electrode layer and the dielectric layer remains A site (Ba) rich even as the diffusion of BaSnO3 progresses, so the sinterability is suppressed. Therefore, in an MLCC having an internal electrode layer formed using the Ni paste of this embodiment, there is less risk of localized sintering irregularities, such as the appearance of abnormally grown grains, occurring at the interface between the internal electrode layer and the dielectric layer, and there is less risk of the internal electrode being broken and the resulting decrease in capacity.

[0024] The Ni paste of this embodiment can contain a solvent and a binder in addition to nickel powder and ceramic powder.

[0025] (Nickel powder) The nickel powder in the present invention can be manufactured by a manufacturing method in which nickel hydroxide powder synthesized by a CVD (chemical vapor deposition) method, a PVD (physical vapor deposition) method, a spray pyrolysis method, and a wet chemical reduction method, or a manufacturing method in which nickel hydroxide powder synthesized by a wet chemical method is heat-treated in a reducing atmosphere to obtain nickel powder, or an atomization method. The powder form of the nickel powder is preferably one having an average particle diameter of 0.01 μm to 1 μm, more preferably 0.05 μm to 0.5 μm, and flake powder can also be used without being limited to particle form. Furthermore, the nickel powder includes nickel alloy materials to which, for example, tungsten, molybdenum, chromium, phosphorus, zinc, precious metals, rare earth metals, etc. are added to give nickel heat resistance, oxidation resistance, etc., in addition to the nickel simple powder obtained by the various manufacturing methods described above. Note that the nickel powder may contain sulfur as an impurity generated in the manufacturing stage, and even if it contains a small amount of sulfur, it has the effect of suppressing the sudden combustion of the resin component and the sintering of the metal component.

[0026] (ceramic powder) The ceramic powder added to the Ni paste according to the present invention is added as a co-material for bringing the sintering characteristics of the internal electrode layer having a low sintering temperature and the dielectric layer having a high sintering temperature closer to each other, and preferably contains barium titanate powder. As described above, the ceramic powder preferably contains barium stannate.

[0027] (solvent) Examples of the solvent for the Ni paste according to the present invention include alcohol, acetone, propanol, ethyl acetate, butyl acetate, ether, petroleum ether, mineral spirits, and other paraffin-based hydrocarbon solvents, acetate-based solvents such as butyl carbitol, terpineol, dihydroterpineol, butyl carbitol acetate, dihydroterpineol acetate, dihydrocarbyl acetate, carbyl acetate, terpinyl acetate, and linalyl acetate, propionate-based solvents such as dihydroterpinyl propionate, dihydrocarbyl propionate, and isobornyl propionate, cellosolves such as ethyl cellosolve and butyl cellosolve, aromatics, diethyl phthalate, and others. Any solvent that can be used for electrode pastes can be used.

[0028] (Binder) As the binder for the Ni paste according to the present invention, a resin binder is preferable, such as ethyl cellulose, polyvinyl acetal, acrylic resin, alkyd resin, etc., and all other resins used in electrode paints can be used.

[0029] According to a second aspect of the present invention, there is provided a Ni paste in which the ceramic powder further contains barium titanate powder in the first aspect. In the Ni paste of this aspect, barium titanate powder is added as a co-material, so that the sintering characteristics of the internal electrode layer having a low sintering temperature and the dielectric layer having a high sintering temperature of the MLCC can be made similar to each other, and the occurrence of structural defects such as cracks, breaks in the internal electrodes, and delamination during firing can be suppressed.

[0030] According to a third aspect of the present invention, there is provided the Ni paste of the first or second aspect, wherein the ceramic powder further includes barium titanate powder containing sulfur. In the Ni paste of this embodiment, the presence of the sulfur-containing barium titanate powder suppresses the thermal decomposition of the binder component on the surface of the nickel particles in the Ni paste and the associated rapid gas generation during the MLCC manufacturing process, so that it is possible to prevent structural defects such as cracks and delamination in the internal electrode layer during the firing stage. Therefore, due to the synergistic effect with the above effect of the barium stannate powder, this embodiment can provide a Ni paste for forming internal electrodes of MLCCs that is highly reliable when voltage is applied and has a long high-temperature load life, with less risk of causing breaks in the internal electrodes and the associated capacity reduction, and can improve manufacturing yields. The form of sulfur support is not particularly limited, and in addition to the case where sulfur powder is mixed in powder form with barium titanate powder, it may be contained as sulfate radicals or coated on barium titanate powder particles. In particular, when containing as sulfate radicals, it is preferable to synthesize sulfate radicals in barium titanate so that organic components such as benzene and impurity elements such as Na do not remain, rather than using sulfate radical-containing compounds such as sodium dodecyl sulfate and sodium dodecylbenzenesulfonate as in the technology described in JP-A-2006-24539.

[0031] The sulfur-containing barium titanate powder to be contained in the Ni paste of this embodiment can be used by using a barium titanate material with normal crystallinity to be sulfur-containing, but it is particularly preferable to use a barium titanate material with high crystallinity. That is, in this embodiment, when a highly crystalline sulfur-containing barium titanate powder with a lattice constant ratio (c-axis to a-axis ratio: c / a ratio) in the range of 1.0040 to 1.0100 is added, a Ni paste can be realized that maintains the continuity of the electrodes in the internal electrode layer during firing and fully exerts the effect of preventing the occurrence of structural defects. In addition, in this embodiment, it is preferable to add the sulfur-containing barium titanate powder having an average particle size of 10 nm to 100 nm, a tetragonal crystal, and a highly crystalline spherical shape. In such a case, this embodiment can provide a Ni paste that has the continuity of the electrodes in the internal electrode layer during firing and fully exhibits the effect of preventing the occurrence of structural defects, and is suitable for forming the internal electrodes of high-quality MLCCs.

[0032] According to a fourth aspect of the present invention, there is provided a Ni paste in the third aspect, in which the barium stannate is contained in a ratio of 1 to 5 mass % relative to the nickel powder, and the barium titanate powder or the barium titanate powder containing sulfur is contained in a ratio of 5 to 25 mass % relative to the nickel powder. In the Ni paste of this embodiment, the barium stannate is contained in a ratio of 1 to 5 mass % relative to the nickel powder, and the barium titanate powder or the barium titanate powder containing sulfur is contained in a ratio of 5 to 25 mass % relative to the nickel powder. It is possible to provide a Ni paste for forming internal electrodes of MLCCs which has an extremely low risk of breakage and the accompanying decrease in capacity, can improve manufacturing yields, is extremely reliable when voltage is applied, and has an extremely long high-temperature load life.

[0033] According to a fifth aspect of the present invention, there is provided a method for producing a Ni paste for forming an internal electrode of a multilayer ceramic capacitor, comprising mixing nickel powder, barium titanate powder or barium titanate powder containing sulfur, and barium stannate powder into a vehicle in which a binder and a solvent are dissolved to produce a Ni paste.

[0034] According to a sixth aspect of the present invention, there is provided a method for producing a multilayer ceramic capacitor, comprising coating the Ni paste according to the first, second or fourth aspect on a ceramic substrate and firing the coated substrate to form an internal electrode containing Ni. According to the present embodiment, due to the effect of maintaining electrode continuity in the internal electrode layer during sintering of the sulfur-containing barium titanate powder and preventing the occurrence of structural defects, and / or the effect of the barium stannate powder in extending the high-temperature load life of the MLCC, the risk of internal electrode breakage and the resulting decrease in capacity is reduced, manufacturing yield can be improved, and a manufacturing method can be provided for an MLCC that is highly reliable when voltage is applied and has a long high-temperature load life.

[0035] According to a seventh aspect of the present invention, there is provided a multilayer ceramic capacitor comprising: a ceramic laminate formed by alternately laminating a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni; and external electrodes formed on an outer surface of the ceramic laminate, wherein the internal electrode layers contain elements Ba, Ti, O, Sn and S. According to this embodiment, due to the sintering retardation effect of Ba contained in the internal electrode layer, the effect of S maintaining the continuity of the electrodes in the internal electrode layer during firing and preventing the occurrence of structural defects, and the effect of Sn extending the high-temperature load life of the MLCC, the risk of breakage of the internal electrodes and the resulting decrease in capacity during production is reduced, the production yield can be improved, and a multilayer ceramic capacitor with high reliability when voltage is applied and a long high-temperature load life can be provided. In the multilayer ceramic capacitor of this embodiment, it is preferable that the internal electrode layers do not contain any of the other elements In, Ga, Zn, Bi, Pb, Ta, and Nb. In such a case, in this embodiment, since the internal electrode layers do not contain these other elements that may diffuse from the internal electrode layers to the dielectric layers during firing during the manufacture of the MLCC and adversely affect the dielectric constant, dielectric loss, temperature characteristics of the MLCC, etc., it is possible to provide an MLCC with a long high-temperature load life without sacrificing the desired MLCC characteristics such as temperature characteristics. In addition, "does not contain other elements" means "does not substantially contain other elements", and "does not substantially contain other elements" means "any of the above other elements is less than 1×10 -3 This means that it is not contained at a concentration of 50% by mass or more.

[0036] 1 is a cross-sectional view showing a schematic structure of a multilayer ceramic capacitor 1. The multilayer ceramic capacitor 1 is configured by attaching an external electrode 4b to a laminate in which internal electrode layers 2 and dielectric layers 3 are alternately laminated. EXAMPLES

[0037] Next, Ni pastes according to examples of the present invention and comparative examples will be described. [Table 1]

[0038] Table 1 shows the composition of 16 types of Ni pastes, four types for each level: A, B, D, and E. Each Ni paste contains nickel powder (Ni powder), barium titanate powder (BT powder), and barium stannate powder.

[0039] For example, for the A level, of the four types of Ni pastes A0, A1, A3, and A5, A0 does not contain barium stannate powder, and A1, A3, and A5 contain 1%, 3%, and 5% barium stannate powder by mass relative to the nickel powder, respectively. The same applies to the mass ratio of barium stannate powder to nickel powder contained in each Ni paste of the B level, D level, and E level.

[0040] (Nickel powder) Two types of nickel powder were used: one with an average particle size of 0.2 μm (hereafter referred to as "Ni02") and the other with an average particle size of 0.3 μm (hereafter referred to as "Ni03"). The Ni pastes of levels A and E contain nickel powder (Ni03) in the composition ratios shown in Table 1, and the Ni pastes of levels B and D similarly contain nickel powder (Ni02).

[0041] (Barium titanate powder) Four types of barium titanate powder were used: one with an average particle size of 50 nm and no sulfur (hereinafter referred to as "BT50"), one with 50 nm and sulfur (hereinafter referred to as "S-BT50"), one with 100 nm and no sulfur (hereinafter referred to as "BT100"), and one with 100 nm and sulfur (hereinafter referred to as "S-BT100"). Each Ni paste of level A and level E contains BT powder (S-BT100) in the composition ratio shown in Table 1, each Ni paste of level B contains BT powder (S-BT50) in the composition ratio shown in Table 1, and each Ni paste of level D contains BT powder (BT50) in the composition ratio shown in Table 1. According to an analysis using a commercially available particle size distribution measuring device, the sulfur-free BT powder (BT100) has an average particle size of 0.09 μm in number distribution and a 10% quantile particle size D 10 is 0.08μm, 50% quantile particle size D 500.11μm, 90% quantile diameter D 90 is 0.20μ m and the specific surface area is 13.9 m 2 / g. For the BT powder, it is preferable to use a highly crystalline barium titanate material having a lattice constant ratio (ratio of c-axis to a-axis: c / a ratio) in the range of 1.0040 to 1.0100. Also, for the BT powder, it is preferable to use a highly crystalline barium titanate material having a lattice barium (Ba) to titanium (Ti) composition ratio (Ba / Ti) of 0.99 to 1.01. The sulfur-containing BT powder (S-BT100) is a powder in which the surface of the BT powder (BT100) is coated with sulfur, and the sulfur is contained in a ratio of 0.1% by weight relative to barium titanate. There is almost no difference in particle size distribution and specific surface area between the sulfur-free BT powder (BT100) and the sulfur-containing BT powder (S-BT100). No aggregation due to sulfur is observed in the sulfur-containing BT powder (S-BT100). In this specification, the "average particle size" generally means the "average particle size in number distribution".

[0042] (Barium stannate powder) As the barium stannate powder, it is preferable to use a powder having an average particle size of about 0.01 to 1.0 μm, and it is more preferable to use a powder having an average particle size of 0.05 μm to 0.6 μm.

[0043] <Example 1: Production of Ni paste A1 etc.> The method of producing Ni paste A1 will be described. As shown in Table 1, the composition of Ni paste A1 is 50% by weight of nickel powder (Ni03) with an average particle size of 0.3 μm, 4.7% by weight (10% by weight relative to nickel powder) of highly crystalline barium titanate powder (S-BT100) containing sulfur with an average particle size of 100 nm, 0.50% by weight (1.0% by weight relative to nickel powder) of barium stannate powder, 7.0% by weight of resin solids (ethyl cellulose powder), 0.5% by weight of dispersant for electrode paste, and 40.33% by weight of solvent (terpineol). These components were prepared in the above ratio and dispersed and mixed by a ceramic three-roll mill to produce Ni paste A1. Similarly, nickel powder (Ni02 or Ni03), highly crystalline barium titanate powder containing or not containing sulfur (S-BT50, S-BT100, BT50 or BT100), and barium stannate powder were prepared in the mass ratios shown in Table 1, and in addition, 7.0% by weight of resin solids (ethyl cellulose powder), 0.5% by weight of electrode paste dispersant, and a solvent (terpineol) in an amount that makes the total 100% by weight were prepared, and dispersed and mixed using a ceramic three-roll mill to produce Ni pastes A3, A5, B1, B3, B5, D1, D3, D5, E1, E3, and E5, respectively.

[0044] <Comparative Example 1: Production of Ni paste A0 etc.> A Ni paste was prepared in the same manner as the preparation of Ni paste A1, except that barium stannate powder was not added and the proportion of the solvent (terpineol) was set to 40.8% by weight instead. Thus, Ni paste A0 was obtained. Similarly, nickel powder (Ni02 or Ni03), sulfur-containing or sulfur-free highly crystalline barium titanate powder (S-BT50, S-BT100, BT50 or BT100) were prepared in the mass ratios shown in Table 1, and in addition, 7.0% by weight of resin solids (ethyl cellulose powder), 0.5% by weight of electrode paste dispersant, and a solvent (terpineol) in an amount that makes the total 100% by weight were prepared, and dispersed and mixed using a ceramic three-roll mill to produce Ni pastes B0, D0, and E0 that do not contain barium stannate powder.

[0045] <Example 2: Production of MLCC (A1) etc.> Ni paste A1 was applied as an internal electrode material by screen printing in a predetermined pattern onto a 0.4 μm thick ceramic green sheet for X5R characteristics, mainly composed of barium titanate with an average particle size of 0.3 μm. Next, multiple ceramic green sheets were stacked together and integrated by heat and pressure bonding to obtain a multilayer laminate. The internal electrode layer was six layers. The laminate was subjected to a binder removal treatment at 500°C or less in an oxidizing atmosphere or an inert atmosphere, cut to a specified size, and then fired in a reducing atmosphere to produce an MLCC element. External electrodes were formed on both end faces of the laminate by applying Cu paste and firing the paste to obtain an MLCC (A1). The screen printing conditions were size 3.2 mm x 2.5 mm (3225 type) and plate making specifications SUS#500CAL-19SH. The conditions for heat-pressing to obtain the multilayer laminate were 80°C, 1×10 4 N / cm 2 , 1 minute. The firing conditions for manufacturing the MLCC body were 1240°C for 1 hour in a nitrogen gas atmosphere containing 2% H2 (Wetter: 35°C), followed by a re-oxidation treatment in a nitrogen atmosphere at 950°C for 1.5 hours. Similarly, by using Ni paste A3, A5, B1, B3, B5, D1, D3, D5, E1, E3 or E5 instead of Ni paste A1 as the internal electrode material, MLCC(A3), MLCC(A5), ..., MLCC(E3) or MLCC(E5), respectively, were obtained.

[0046] <Comparative Example 2: Manufacturing of MLCC (A0) etc.> In the manufacturing method of the above MLCC (A1), an MLCC (A0) was obtained by using Ni paste A0 instead of Ni paste A1 as the internal electrode material. Similarly, MLCC(B0), MLCC(D0), and MLCC(E0) were obtained in that order by using Ni pastes B0, D0, and E0, respectively, as the internal electrode material.

[0047] (Interlayer thickness and barium stannate content) FIG. 2 is a cross-sectional photograph of an optical microscope of a laminate of MLCCs after firing in which the internal electrode layers are formed using four levels of Ni paste, A, B, D, and E, each of which is four types, for a total of 16 types. At each level, there is no significant difference in the interlayer thickness (thickness of the dielectric layer) between the MLCC (A0) of the comparative example formed using Ni paste (A0, etc.) that does not contain barium stannate, and the MLCC (A1), MLCC (A3), MLCC (A5), etc. of the embodiment formed using Ni paste (A1, A3, A5, etc.) that contains barium stannate and has a different mass ratio of barium stannate to Ni powder. The difference in thickness between layers is within ±3%. In addition, the continuity of all the internal electrode layers is good. It can be seen that there is no undesirable phenomenon from the viewpoint of the high-temperature load life of MLCCs, such as "during firing, barium stannate liberated from the internal electrode layer moves to the dielectric layer, increasing the thickness of the dielectric layer, and at the same time, the thickness of the internal electrode layer is locally reduced."

[0048] (Capacitance and amount of barium stannate added) 3A and 3B are graphs showing the relationship between the amount of barium stannate added to Ni paste and the capacitance of MLCCs in which internal electrode layers are fabricated using the Ni paste, for four levels, A, B, D, and E. For each of the four levels, A, B, D, and E, and four types each, for a total of 16 types of MLCCs, ten MLCC samples were fabricated, and the capacitance was measured to calculate the average value. In the MLCC in which the internal electrode layer is produced using Ni paste of level A and level E, which contains Ni powder with an average particle size of 0.3 μm and sulfur-containing BT powder with an average particle size of 100 nm, the capacitance of the MLCC tends to decrease as the amount of barium stannate added increases. However, such a tendency is not observed in the MLCC in which the internal electrode layer is produced using Ni paste of level B (BT powder containing sulfur) and level D (BT powder not containing sulfur), which contains Ni powder with an average particle size of 0.2 μm and BT powder with an average particle size of 50 nm. In particular, in the case of level B, when the amount of barium stannate added to the Ni paste is 1 to 3 mass% (or 0.5 to 3 mass%) with respect to the Ni powder, the capacitance of the MLCC produced is larger than when barium stannate is not added. The increase in the above-mentioned capacitance seen in level B is considered to be due to the synergistic effect of the addition of barium stannate and the addition of sulfur to the BT powder. In addition, in the MLCCs in which the internal electrode layers were fabricated using Ni pastes of levels A and E, the amount of barium stannate added was As the content increases, the capacitance of the MLCC tends to decrease, but in the case of level A, the decrease in capacitance compared to MLCC (A0) is approximately -8% for MLCC (A3) and approximately -9% for MLCC (A5), and the decrease rate saturates. Similarly, in the case of level E, the decrease in capacitance compared to MLCC (E0) is approximately -11% for MLCC (E3) and approximately -12% for MLCC (E5), and the decrease rate saturates. The difference in the decrease rate of capacitance between levels A and E is thought to be due to the amount of barium titanate added.

[0049] (DF (dielectric tangent) and barium stannate addition amount) Figure 4 is a graph showing the relationship between the amount of barium stannate added to Ni paste and the measured DF (dielectric tangent) of an MLCC in which an internal electrode layer is fabricated using the Ni paste, for four levels: A, B, D, and E. The measurement conditions were 20°C and 1 kHz. Only the average DF measurement values ​​are plotted. Except for the exceptions where the amount of barium stannate added to the Ni paste is within the range of 0 to 1 mass% relative to the Ni powder at level B, the DF tends to decrease as the amount of barium stannate added to the Ni paste increases at all levels. In the above exceptions, the DF was almost constant regardless of the amount of barium stannate added. It was also found that the relationship between the DF and the amount of barium stannate added in the capacitance showed almost the same tendency of decrease.

[0050] (High temperature load test) 5A is a graph (Weibull plot) showing the relationship between time t and failure rate F in a high-temperature load test of MLCCs in which internal electrode layers were fabricated using the four types of Ni paste of level A of the present invention. The horizontal axis shows the natural logarithm ln(t) of time t (hr), and the vertical axis shows the function ln(ln((1 / (1-F))) of failure rate F. Ten MLCCs were fabricated for each of the four types of Ni paste, and a high-temperature load test was performed at a temperature of 160°C and an applied voltage of 100V. The time t and failure rate F were plotted using the above functions each time one MLCC failed. The MLCCs (A1), (A3) and (A5) whose internal electrodes were fabricated using Ni paste containing barium stannate had a longer time to failure than the MLCC (A0) whose internal electrodes were fabricated using Ni paste not containing barium stannate. It can also be seen that the MLCC (A1), in which the amount of barium stannate added to the Ni paste was 1% by mass relative to the Ni powder, had the longest time to failure. The time until each MLCC failed (failure time) was defined as the time required for the IR (insulation resistance) of the MLCC to decrease to one-tenth of its initial value.

[0051] FIG. 5B is a graph (Weibull plot) similar to FIG. 5A, showing the relationship between time t and failure rate F in a high-temperature load test of MLCCs in which internal electrode layers were fabricated using Ni pastes of standards B, D, and E.

[0052] [Table 2]

[0053] (MTTF (Mean Time to Failure) and m value) Table 2 shows the MTTF (mean time to failure) and m value obtained from the regression line of the Weibull plot for each of the four levels (A, B, D, and E) and four types each (16 types in total). Figure (6-1) is a graph showing the relationship between the amount of barium stannate added to the Ni paste and the MTTF for each of the four levels, A, B, D, and E. Figure (6-2) is a graph showing the relationship between the MTTF value for each level, normalized by dividing the MTTF value by the MTTF value when the amount of barium stannate added to the Ni paste is 0 mass%, with the ordinate showing the MTTF value and the abscissa showing the amount of barium stannate added to the Ni paste. At any level, the MTTF is longest when the amount of barium stannate added to the Ni paste is 1% by mass relative to the Ni powder, and the MTTF becomes shorter as the amount of addition moves away from 1% by mass. The ratio of the MTTF when the amount of barium stannate added to the Ni paste is 1% by mass relative to the Ni powder to the MTTF when no barium stannate is added is about 1.4 times at the smallest level D and about 2.6 times at the largest level A. From the viewpoint of producing an internal electrode layer of an MLCC with a long MTTF (mean time to failure), the amount of barium stannate added to the Ni paste is preferably 0.5 to 3 mass% relative to the Ni powder, and more preferably 1 to 2 mass%. In this specification, the expression "X to Y mass%" generally means "X mass% or more and Y mass% or less." (The same applies to amounts with other units.)

[0054] (IR (insulation resistance)) Figure 7 is a graph showing the relationship between the amount of barium stannate added to the Ni paste of standard A and the measured IR (insulation resistance) value of an MLCC in which the internal electrode layer was fabricated using the Ni paste. The measured IR (insulation resistance) value did not change significantly even when the amount of barium stannate added was changed. This also shows that the added barium stannate does not diffuse into the dielectric layer and cause a significant deterioration in insulation resistance.

[0055] (TCC (Temperature Change of Capacitance)) FIG. 8 is a graph showing the measured values ​​of TCC (temperature change of capacitance) of MLCCs in which internal electrode layers were fabricated using Ni paste A1 (addition amount of barium stannate is 1 mass% / Ni) and Ni paste A5 (same amount is 5 mass% / Ni) of standard A. TCC shows the rate of change as a percentage based on the capacitance at 25°C. The rectangle R shown by the dotted line shows the range satisfying the X5R characteristic, that is, the rate of change of capacitance is ±15% or less in the temperature range of -55°C to 85°C. The measured values ​​of TCC did not show a large change even when the amount of barium stannate added was changed, and the MLCC satisfied the X5R characteristic regardless of the amount of barium stannate added. It is generally known that when Ba is excessive in the Ni paste, the temperature characteristic of the MLCC shifts downward due to segregation of Ba, and deviates from the range of the X5R characteristic at high temperatures. In Ni pastes A1 and A5, the amount of BaSnO3 added is small, at 1 mass% / Ni or 5 mass% / Ni, so it is believed that segregation of Ba did not occur and no significant change was observed in the measured TCC value. This assumption that segregation of Ba did not occur is also supported by the fact that, as shown in the photograph in Figure 2, there is almost no difference in the interlayer film thickness after sintering due to the amount of BaSnO3 added.

[0056] (Relationship between the amount of barium titanate and barium stannate added and the characteristics of MLCC) Figures (9-1) and (9-2) are graphs showing how the characteristics of an MLCC made using the Ni paste of the present invention change when the amount of BT powder and the amount of barium stannate added are changed when the Ni paste of the present invention contains barium stannate and barium titanate (BT powder). When comparing the cases where the amount of barium titanate (BT) powder added is 10 mass% / Ni (level A) and 15 mass% / Ni (level E), regardless of the amount of barium stannate added, the capacitance and DF (dielectric tangent) are both higher in level E, which has a higher amount of barium titanate powder added, than in level A. Furthermore, when the amount of barium titanate added is fixed, the capacitance decreases gradually up to 3 mass% / Ni, but remains almost unchanged beyond that. It can also be seen that the DF (dielectric tangent) decreases gradually in both cases as the amount of barium stannate added increases.

[0057] (Relationship between the amount of BT powder added and the characteristics of MLCC) 10A and 10B are graphs showing how the characteristics of an MLCC made using a Ni paste of the present invention change when the amount of BT powder added is changed when the Ni paste contains 1 mass% Ni of barium stannate and barium titanate (BT powder). As can be seen from Figures (10-1) and (10-2), when comparing the cases where the amount of barium titanate (BT) powder added is 10 mass% / Ni (A1) and 15 mass% / Ni (E1), the capacitance and DF (dielectric tangent) increase as the amount of barium titanate powder added increases. This is thought to be because, as the amount of barium titanate powder added increases, the sintering of the electrodes slows down, the electrode coverage rate increases, and the thickness of the dielectric sheet generally increases due to the diffusion of barium titanate powder to the dielectric element side. However, as can be seen from the Weibull plot in Figure (10-3) and Figure (10-4), there was almost no change in the MTTF (mean time to failure) in HALT (high temperature load testing) regardless of the amount of barium titanate (BT) powder. From this, it is considered that changing the amount of barium titanate (BT) powder added is not very effective in providing a Ni paste capable of improving the high temperature load life, which is the object of the present invention.

[0058] (Relationship between the presence or absence of sulfur in BT powder and the characteristics of MLCC) 11A and 11B are graphs showing how the characteristics of an MLCC manufactured using a Ni paste according to the present invention change depending on whether or not the BT powder contains sulfur when the Ni paste contains barium stannate and barium titanate powder (BT powder). The graphs show the measured values ​​of various properties of MLCCs in which internal electrodes were fabricated using Ni paste B1 as "sulfur-free" and Ni paste D1 as "sulfur-free". These measurements have been presented previously and are shown again in the graphs for comparison purposes. Both Ni pastes B1 and D1 contain 1% by weight barium stannate relative to the Ni powder, as shown in Table 1. Figure (11-1) is a graph comparing capacitance. It can be seen that the capacitance of the MLCC (B1) in which the BT powder contains sulfur is about 3% larger than that of the MLCC (D1) in which the BT powder does not contain sulfur. Figure (11-2) is a graph comparing DF (dielectric tangent). The MLCC (B1) in which the BT powder contains sulfur has a DF that is about 4% larger than the MLCC (D1) in which the BT powder does not contain sulfur. Considering the relationship between capacitance and DF, it can be seen that sulfur does not have a significant effect on DF. Figure (11-3) is a Weibull plot, and Figure (11-4) is a graph comparing the MTTF (mean time to failure) calculated by linear regression from the Weibull plot. It can be seen that the MTTF of the MLCC (B1) in which the BT powder contains sulfur is about 27% larger than that of the MLCC (D1) in which the BT powder does not contain sulfur.

[0059] (TMA (Thermomechanical Analysis)) Ten types of Ni pastes (A0, A1, A3, A5, B0, B1, B3, B5, D1 and E1) were prepared from Ni pastes having the compositions shown in Table 1 by the above-mentioned manufacturing method. Figures 12A and 12B are graphs showing the results of TMA (thermo-mechanical analysis) measurements of these Ni pastes, comparing four or two of them at a time. For TMA (thermo-mechanical analysis), each Ni paste was dried at 100°C, the dried powder was fired at 340°C for 20 min to remove the binder, and the debindered sample was crushed in an agate mortar to produce a fine powder. Using a jig with a diameter of 1.6 cm, a pressure of approximately 1420 kgf / cm was applied. 2 A pellet was prepared by cutting the φ1.6 cm pellet into a 5 mm square using a cutter to prepare a measurement sample. The measurement was performed under the following conditions: temperature rise 10℃ / min, TOP temperature 1300℃, and firing atmosphere of H2:N2=98:2.

[0060] Figure (12-1) is a graph comparing the TMA measurement results of four types of Ni paste (Level A) when the amount of barium stannate added was changed. When barium stannate powder was added, sintering proceeded faster from 300°C compared to when no barium stannate powder was added (A0). In particular, when the amount added was 5 mass% Ni (A5), sintering shifted overall to the lower temperature side. The lowering of sintering temperatures due to the effect of tin was clearly observed.

[0061] Figure (12-2) is a graph similar to Figure (12-1) comparing the TMA measurement results of four types of Ni paste (Level B) when the amount of barium stannate added was changed. Level B paste is characterized by smaller average particle diameters of both Ni powder and sulfur-containing BT powder compared to Level A paste. As with Level A Ni paste, when barium stannate powder is added, sintering proceeds faster from 300°C compared to when no barium stannate powder is added (B0). In particular, when the amount of added Ni is 5 mass% (B5), sintering has shifted overall to the lower temperature side. The effect of tin on the lower sintering temperature was clearly seen.

[0062] Figure (12-3) is a graph comparing the TMA measurement results of two types of Ni pastes (A1 and E1) in which the barium titanate powder contains sulfur, but the amount of barium stannate added is constant and the amount of barium titanate powder added is different. Compared to the case where the amount of barium titanate powder added is 10 mass% / Ni (A1), the Ni paste (E1) in which the amount of barium titanate powder added is increased to 15 mass% / Ni has a greater overall delay in sinterability, which is thought to be because the sintering retarding effect of the added barium titanate exceeds the sintering promoting effect of the tin in the barium stannate.

[0063] In Figure (12-4), both contain barium stannate powder, but Ni powder and barium titanate powder are also included. This is a graph comparing the TMA measurement results of two types of Ni pastes (B1 and D1), which have the same nickel powder size but differ in whether the barium titanate powder contains sulfur. The sintering characteristics of both are almost the same up to 900°C. From 900°C to 1200°C, the sintering of the sulfur-containing Ni paste (D1) is delayed compared to the sulfur-free Ni paste (B1). This is thought to be due to the sintering inhibition effect of the sulfur contained in the barium titanate powder. [Industrial Applicability]

[0064] According to the present invention, by preparing the internal electrode layer using Ni paste containing barium stannate powder, it is possible to provide an MLCC having a long high-temperature load life and a large electric capacity. Also, by preparing the internal electrode layer using Ni paste containing sulfur-containing barium titanate powder in addition to barium stannate powder, it is possible to provide an MLCC having a long high-temperature load life and a large electric capacity. [Explanation of symbols]

[0065] 1. Multilayer ceramic capacitors 2 Internal electrode layer 3 Dielectric Layer 4 External electrode R Rectangle represented by dotted lines

Claims

1. A Ni paste for forming an internal electrode of a multilayer ceramic capacitor, the Ni paste containing nickel powder and ceramic powder, the ceramic powder containing barium stannate.

2. The Ni paste of claim 1 , wherein the ceramic powder comprises barium titanate powder.

3. The Ni paste according to claim 1 or 2, wherein the ceramic powder contains sulfur-containing barium titanate powder.

4. The barium stannate is contained in a ratio of 1 to 5% by mass with respect to the nickel powder, and the barium titanate powder or the barium titanate powder containing sulfur is contained in a ratio of 5 to 25% by mass with respect to the nickel powder. The Ni paste according to claim 3.

5. A method for producing a Ni paste for forming an internal electrode of a multilayer ceramic capacitor, comprising mixing nickel powder, barium titanate powder or barium titanate powder containing sulfur, and barium stannate powder into a vehicle in which a binder and a solvent are dissolved to produce a Ni paste.

6. A method for producing a multilayer ceramic capacitor, comprising coating a ceramic substrate with the Ni paste according to claim 1, 2 or 4 and firing the coated substrate to form an internal electrode containing Ni.

7. A ceramic laminate including a plurality of ceramic dielectric layers and a plurality of internal electrode layers containing Ni alternately laminated together, and an external electrode formed on an outer surface of the ceramic laminate, The internal electrode layers contain the elements Ba, Ti, O, Sn and S.

Citation Information

Cited By

  • Electroplating end electrode-based vehicle gauge soft terminal multilayer ceramic capacitor structure and process

    CN120998686A